Psycholinguistic Meaning of the Concept of “Faith” - Tamara Khomulenko; Oleksiy Kuznetsov (Психолінгвістика)
The article presents the results of a free associative experiment aimed at studying the verbalized concept of “faith” in the ordinary linguistic consciousness. The sample consisted of 487 people, speakers both of Russian and Ukrainian languages (15-67 years old) in an equal ratio of male and female. The article provides an analysis of the frequencies of the first reaction to the word-stimulus “faith” and the five reactions together, and the results of the clustering of high-frequency associations. The psycholinguistic meaning of the concept of faith was considered by us as an ordered unity of all the semantic components of the lexeme “faith”, which are really connected with this sound form in the consciousness of the speakers of the Russian and Ukrainian languages. The study showed that the concept of “faith” is expressed in the nuclear psycholinguistic meaning “hope”. The results of the experiment suggest that the associative field of the concept “faith” is represented by theological (religious) and moral semes, reflected in the peripheral psycholinguistic meanings – “love”, “religion”, “God”, “church” and many other meanings of the extreme periphery. It was shown that faith represents the “female name”, which acts as a detotat of females, which also explains the high frequency of personalized reactions. The etymological analysis of the lexeme “faith” allowed us to correlate the primary meanings of this concept with its meanings in the content of the modern ordinary consciousness and to conclude that some of the original meanings of faith remained (“trust”, “confidence”, “oath”, “verity”, “religion”, “deity”), and some of the meanings have been lost. In general, our results are confirmed in the works of both foreign and domestic scientists devoted to the analysis and description of the concept of “faith”, which is characterized by several semantic levels, ambivalence, high-frequency associates of theological and moral semantics, the presence of metaphorical and emotive values.